Eksperimen Pembelajaran Matematika Dengan Strategi Student Team Achievement Division (STAD) Dan Think Pair Share (TPS) Terhadap Hasil Belajar Ditinjau Dari Keaktifan Siswa - Adiningsih, Kiki; , Drs. Ariyanto, M.Pd (2017)
This study aims to examine (1) the effect of mathematics learning with Student Team Achievement Division and Think Pair Share strategy on the result of mathematical learning , (2) the effect of students' learning activeness on the result of mathematical learning, (3) the interaction between the Student Team Achievement Division and Think Pair Share strategy seen from the students activeness on mathematics learning. The type of the research is experiment with quasi experimental design. The population of the research was all students of VII Grade of SMP Negeri 1 Nguter year 2016/2017. The research sample consisted of two classes namely VII B grade as Student Team Achievement Division class and VII A grade as Think Pair Share class. The sampling technique used is cluster random sampling. Technique of collecting data with method test, questionnaire method, and documentation. Technique for analyzing data uses is two-way analysis of variance test with unequal cells, previously performed prerequisite analysis to test for normality and homogeneity test. From the results of data analysis at the level of 5% was obtained that: (1) there is effect of Student Team Achievement Division and Think Pair Share strategy on the result of mathematics learning with FA = 4.352 (2) there is effect of students' learning activeness on the result of mathematics learning with FB = 311. 107 (3) there is no interaction between of Student Team Achievment Division and Think Pairs Share strategy seen of the students' learning activeness on the result of mathematics learning with FAB = 0.206.